Quantitative Analysis of the Effect of Fluorescent Labels on DNA Strand Displacement Reaction - Masato Toyonari; Kaori Aso; Takashi Nakakuki (Micromachines, 2024)
DNA chemical reaction networks can perform complex information processing through careful design of reaction kinetics, which involves the reaction network structure, rate constants, and initial concentrations. The toehold-mediated strand displacement reaction (TMSDR) is a key mechanism in creating DNA circuits, offering a rational design approach by integrating individually designed TMSDRs. Tools such as VisualDSD and NUPACK facilitate the efficient design of these systems by allowing precise tuning of reaction parameters. However, discrepancies between simulated and experimental results can occur, often due to the modification of reporter molecules. Recently, fluorophore dyes and quenchers were found to significantly impact the dynamics of irreversible TMSDRs, altering them by nearly two orders of magnitude. The impact on reaction dynamics varies with the modification site of these reporters. This study examines the mechanisms of reporter modifications affecting reversible TMSDRs, influencing transient and steady-state characteristics. This is crucial for DNA circuit design, which integrates reversible and irreversible TMSDRs. Our findings indicate that modifying fluorescent dye and quencher an appropriate distance apart (e.g., toehold length) can minimize adverse effects on the DNA reaction dynamics while ensuring effective FRET, therefore improving the accuracy of experimental verification for DNA reaction systems.